The Identification of Potential and Development of Food and Beverages Made from Agricultural Products in Cisangkal Tourism Village - Purnamasari, Ratih Pitria; Ni Gusti Made Kerti Utami; Affandi, Dodi; Suparman, Maksum; Roesfian, Erfin (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2023)
This research aims to identify the potential of the typical agricultural products of Cisangkal WIsata Village, namely mangosteen, tubers, durian, honje and several other agricultural products which are the main income of the community, developed not only as agricultural products, but have added value so that they can become superior products owned by residents to increase the income of the surrounding community. According to Kotler (2000) regarding Product Development Strategy, there are 3 stages of product development strategy that can be carried out, namely a quality improvement strategy, a privilege improvement strategy and a style (appearance) improvement strategy. Everything is done so that the product can have added value for commercialisation. The research method used is a direct survey method to obtain information related to agricultural products in the Cisangkal Tourism Village. The research team also used interview and observation methods to obtain the data. Based on the research results, it was found that one of the identified agricultural products that can be developed is Honje (Kecombrang) forest, which is spread over approximately 1 ha in plantations owned by residents and village owners, only used for daily household needs, and only by 1 person who produces it into Honje Juice using simple equipment and technology. From the results of this research, it can be concluded that forest honje (combrang) is one of the agricultural products that has the potential to be developed into a food and beverage product that can be commercialised, so that it will be able to improve the economy of the residents of Cisangkal Tourism Village. Strengthening knowledge and skills for the residents of Cisangkal Tourism Village regarding product development, product packaging, hygiene, sanitation and also marketing (branding). Furthermore, this research was also carried out as a basis or reference in carrying out community service activities that will be carried out by the research team as an implementation of the research carried out.